Micro-nano copper solder paste and preparation method thereof

By preparing micro-nano copper particles with nano-protrusion structures on their surfaces and adding antioxidants and thixotropic agents, the problem of low sintering activity of micro-nano copper solder paste was solved, achieving low-temperature sintering interconnection and simplifying the packaging process, making it suitable for the field of electronic packaging.

CN117548905BActive Publication Date: 2026-11-06NIO TECH ANHUI CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311769710.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-20
Publication Date
2026-11-06
Estimated Expiration
2043-12-20

AI Technical Summary

Technical Problem

Existing micro/nano copper solder pastes used for power device packaging have low sintering activity, resulting in high sintering temperatures and complex packaging processes.

Method used

By preparing micro- and nano-sized copper particles, a reduction method using a primary copper source and a secondary metal source is employed to form micro- and nano-sized copper particles with nano-protrusion structures on their surface. Antioxidants and thixotropic agents are then added to prepare micro- and nano-sized copper solder paste, thereby improving its sintering activity.

Benefits of technology

It enables sintering interconnection of substrates such as copper, silver, gold, and nickel at low temperatures, simplifies the packaging process, is suitable for different application scenarios, and is suitable for mass production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117548905B_ABST
    Figure CN117548905B_ABST
Patent Text Reader

Abstract

This invention relates to the field of electronic packaging materials technology, specifically providing a micro / nano copper solder paste and its preparation method, aiming to solve the problem of high sintering temperatures caused by low sintering activity in existing solder pastes used for power device packaging. The preparation method of the micro / nano copper solder paste of this invention includes the following steps: S1: preparing micro / nano copper particles; S2: dissolving solder paste additives in an organic solvent to obtain a mixed paste additive; S3: mixing the micro / nano copper particles with the mixed paste additive to obtain the micro / nano copper solder paste; the micro / nano copper particles are obtained by sequential reduction using a primary copper source and a secondary metal source, where the oxidation capacity of the secondary metal source is less than that of the primary copper source. This invention uses two copper sources with different oxidation capacities to prepare micro / nano copper particles, which can form micro / nano copper particles with a raised surface structure, greatly increasing the specific surface area of ​​the micro / nano copper particles. This results in the prepared micro / nano copper solder paste having high sintering activity, lowering the sintering temperature, and increasing the shear strength of the sintered solder joints.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of electronic packaging materials technology, specifically providing a micro / nano copper solder paste and its preparation method. Background Technology

[0002] Electronic packaging technology provides electrical interconnection, physical protection, and mechanical support for semiconductor devices operating under specific conditions. Therefore, the interconnect materials that connect chips or devices to the entire system play a crucial role in maintaining the stable operation of the entire system. As modern electronic products continue to evolve towards miniaturization, high density, high power, and multifunctionality, the demand for electronic devices to operate in high-temperature environments is increasing. Fields such as aerospace, automotive electronics, weaponry, and sensing technology require more robust electronic packaging technologies to enable semiconductor devices to maintain more reliable and stable long-term operation. These devices must be able to maintain switching speed, node temperature, and power density under extreme temperature conditions. Currently used wide-bandgap semiconductors such as SiC and GaN can well meet these requirements and have good high-temperature reliability. However, a comprehensive packaging and interconnection technology system for high-power devices has not yet been established, and the chip interconnect materials used need to withstand operating temperatures as high as 300°C during device operation.

[0003] Traditional soldering materials used for chip interconnects have low melting points and remelt at 300°C, leading to reliability issues in electronic devices. Lead-based and gold-based high-temperature solders also pose problems such as environmental pollution and high cost. Metal nanoparticles, with their small size and high specific surface area, can achieve sintering interconnection between particles at temperatures far below their melting points (150°C to 350°C). The resulting metal bulk also has a service temperature close to its own bulk melting point. In particular, micro-nano copper paste, with copper particles as the main component, is expected to become the main material for next-generation high-power electronic packaging due to its low price, excellent performance, and environmentally friendly characteristics.

[0004] However, existing micro / nano copper solder pastes used for power device packaging still suffer from low sintering activity and high sintering temperatures during interconnection, leading to complex packaging processes for power devices. Summary of the Invention

[0005] The present invention aims to solve the above-mentioned technical problems to a certain extent, namely, to solve the problem that the existing solder paste used for power component packaging has a high sintering temperature due to its low sintering activity.

[0006] In a first aspect, this application provides a method for preparing micro / nano copper solder paste, the method comprising the following steps:

[0007] S1: Preparation of micro / nano copper particles;

[0008] S2: Dissolve the solder paste additive in an organic solvent to obtain a mixed paste additive;

[0009] S3: Mix micro / nano copper particles with paste additives to prepare micro / nano copper solder paste;

[0010] The micro-nano copper particles are obtained by sequential reduction using a primary copper source and a secondary metal source, wherein the oxidation capacity of the secondary metal source is less than that of the primary copper source.

[0011] In the preferred embodiment of the above-mentioned method for preparing micro / nano copper solder paste, the secondary metal source is a secondary copper source, and the steps for preparing micro / nano copper particles specifically include: S11: preparing a reducing agent solution, a primary copper source solution, and a secondary copper source solution respectively; S12: mixing the primary copper source solution and the reducing agent solution to react and obtain a first reaction solution; S13: mixing the secondary copper source solution with the first reaction solution to react and obtain a second reaction solution; S14: centrifuging and drying the second reaction solution to obtain micro / nano copper particles; wherein, the reducing agent solution and / or the primary copper source solution contain a coating agent.

[0012] In the preferred embodiment of the above-mentioned method for preparing micro / nano copper solder paste, in step S11, the step of preparing the reducing agent solution specifically includes: dissolving the coating agent and the reducing agent in a first solvent to obtain the reducing agent solution; and / or, the step of preparing the primary copper source solution specifically includes: dissolving the primary copper source in a second solvent to obtain the primary copper source solution; and / or, the step of preparing the secondary copper source solution specifically includes: dissolving the secondary copper source in a third solvent to obtain the secondary copper source solution.

[0013] In the preferred embodiment of the above-mentioned method for preparing micro / nano copper solder paste, the coating agent includes at least one of polyvinylpyrrolidone and hexadecyltrimethylammonium bromide; and / or, the reducing agent includes at least one of sodium hypophosphite, sodium borohydride, hydrazine hydrate and ascorbic acid; and / or, the primary copper source includes at least one of copper sulfate, copper formate, copper acetate and copper hydroxide; and / or, the secondary copper source includes at least one of cuprous chloride and cuprous sulfate.

[0014] In the preferred embodiment of the above-mentioned method for preparing micro / nano copper solder paste, the first solvent and / or the second solvent and / or the third solvent include at least one of ethylene glycol, polyethylene glycol, diethylene glycol and propylene glycol.

[0015] In the preferred embodiment of the above-mentioned method for preparing micro / nano copper solder paste, the concentration range of the coating agent is 0.02 mol / L to 1.0 mol / L; and / or, the concentration range of the reducing agent is 0.4 mol / L to 3.0 mol / L; and / or, the concentration range of the primary copper source solution is 0.2 mol / L to 1 mol / L; and / or, the concentration range of the secondary copper source solution is 0.01 mol / L to 0.5 mol / L.

[0016] In the preferred embodiment of the above-mentioned method for preparing micro / nano copper solder paste, in step S2, the solder paste additive includes at least one of an antioxidant and a thixotropic agent; and / or, the organic solvent includes at least one of ethylene glycol, diethylene glycol, glycerol and α-terpineol.

[0017] In the preferred embodiment of the above-mentioned method for preparing micro / nano copper solder paste, in step S2, the paste additive satisfies at least one of the following conditions: the antioxidant includes at least one of ascorbic acid, formic acid, citric acid, glucose, and adipic acid; the thixotropic agent includes at least one of castor oil and polyamide; the total weight percentage of the organic solvent, the antioxidant, and the thixotropic agent is 100%, wherein the weight percentage of the organic solvent is 70% to 90%, the weight percentage of the antioxidant is 5% to 20%, and the weight percentage of the thixotropic agent is 0.1% to 10%.

[0018] In the preferred embodiment of the above-mentioned method for preparing micro / nano copper solder paste, the particle size range of the micro / nano copper particles is 50nm to 1000nm.

[0019] In a second aspect, this application provides a micro / nano copper solder paste. The micro / nano copper solder paste of the present invention is prepared by the preparation method described in the first aspect. The micro / nano copper solder paste of the present invention comprises micro / nano copper particles and a paste mixing agent. The total weight percentage of the micro / nano copper particles and the paste mixing agent is 100%. The weight percentages of the micro / nano copper particles and the paste mixing agent are as follows: micro / nano copper particles 50% to 85%; paste mixing agent 15% to 50%.

[0020] Using the above technical solution, micro / nano copper particles obtained by sequential reduction using a primary copper source and a secondary metal source are mixed with a paste additive to obtain micro / nano copper solder paste. The primary copper source, after reduction, is used to grow the micro / nano copper particles. Cuprous ions, with weak oxidizing properties, serve as the secondary copper source for the nano-protrusion structures on the copper core surface, achieving polycrystalline growth of the copper core surface in solution. The resulting submicron copper particles possess a large number of surface nano-protrusion morphologies, significantly increasing the specific surface area of ​​the micro / nano copper particles. This unique high specific surface area enables them to undergo sintering interconnection at relatively low temperatures. The excellent activity of the prepared micro / nano copper solder paste results in high sintering activity, enabling the sintering interconnection of copper, silver, gold, nickel, and other substrates at low temperatures. Furthermore, the addition of antioxidants and thixotropic agents to the copper paste eliminates the need for additional acidic or reducing atmospheres, allowing the sintering process to be completed in air, nitrogen, or vacuum atmospheres. The viscosity of the paste can be controlled by adjusting the thixotropic agent, making it suitable for various industrial applications. The preparation method of this invention is novel and suitable for large-scale production, applicable to the field of electronic packaging, especially in the field of low-temperature sintering interconnection. Attached Figure Description

[0021] The preferred embodiments of the present invention are described below with reference to the accompanying drawings, in which:

[0022] Figure 1 This is a flowchart of the preparation method of the micro / nano copper solder paste of the present invention;

[0023] Figure 2 This is a flowchart of the preparation method of the micro / nano copper particles of the present invention;

[0024] Figure 3 Scanning electron microscope image of micro / nano copper particles with no protrusions on the surface;

[0025] Figure 4 This is a scanning electron microscope image of micro / nano copper particles with tiny protrusions on their surface;

[0026] Figure 5 This is a scanning electron microscope image of micro / nano copper particles with a large protrusion structure on their surface. Detailed Implementation

[0027] Preferred embodiments of the present invention will now be described with reference to the accompanying drawings. Those skilled in the art should understand that these embodiments are merely illustrative of the technical principles of the present invention and are not intended to limit the scope of protection of the present invention.

[0028] Preferred embodiments of the present invention will now be described with reference to the accompanying drawings. Those skilled in the art should understand that these embodiments are merely illustrative of the technical principles of the present invention and are not intended to limit the scope of protection of the present invention.

[0029] Unless otherwise stated, the terms used in this application have their common meanings as commonly understood by those skilled in the art. Unless otherwise stated, the values ​​of the parameters mentioned in this application can be measured using various measurement methods commonly used in the art (e.g., they can be tested according to the methods given in the embodiments of this application).

[0030] The list of items connected by the term "at least one of" or other similar terms can mean any combination of the listed items. For example, if items A and B are listed, then the phrase "at least one of A and B" means only A; only B; or A and B. In another instance, if items A, B, and C are listed, then the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may contain a single component or multiple components. Item B may contain a single component or multiple components. Item C may contain a single component or multiple components.

[0031] The present application will be further described below with reference to specific embodiments. It should be understood that these specific embodiments are for illustrative purposes only and are not intended to limit the scope of the present application.

[0032] Please see Figure 1 , Figure 1 This is a flowchart of the preparation method of the micro / nano copper solder paste of the present invention.

[0033] like Figure 1 As shown, the present invention provides a method for preparing micro / nano copper solder paste, the preparation method comprising the following steps:

[0034] S1: Preparation of micro / nano copper particles;

[0035] S2: Dissolve the solder paste additive in an organic solvent to obtain a mixed paste additive;

[0036] S3: Mix micro / nano copper particles with paste additives to prepare micro / nano copper solder paste;

[0037] The micro-nano copper particles are obtained by sequential reduction using a primary copper source and a secondary metal source, with the secondary metal source having a lower oxidation capacity than the primary copper source.

[0038] Micro-nano copper particles, obtained by sequential reduction using a primary copper source and a secondary metal source, are mixed with a paste additive to obtain micro-nano copper solder paste. The primary copper source, after reduction, is used to grow micro-nano copper particles, while the secondary metal source, after reduction, is used to grow protruding nanocrystals on the surface of the micro-nano copper particles. This results in a protruding structure on the surface of the prepared micro-nano copper particles, which greatly increases the specific surface area of ​​the micro-nano copper particles. Consequently, the prepared micro-nano copper solder paste exhibits high sintering activity, enabling the sintering interconnection of substrates such as copper, silver, gold, and nickel at low temperatures.

[0039] It should be noted that the present invention does not impose any restrictions on the secondary metal source. For example, the secondary metal source can be a secondary copper source, or it can be any other possible metal, as long as the oxidation ability of the secondary metal source is less than that of the primary copper source, and it can form nanocrystals on the surface of the micro-nano copper particles formed after the reduction of the primary copper source, etc. Such adjustments and changes to the specific setting type of the secondary metal source do not deviate from the principle and scope of the present invention, and should all be included within the protection scope of the present invention.

[0040] The preparation method of the micro / nano copper solder paste of the present invention will be introduced below, taking a secondary metal source as a secondary copper source as an example.

[0041] Specifically, please refer to Figure 2 , Figure 2 This is a flowchart of the preparation method of the micro / nano copper particles of the present invention.

[0042] like Figure 2 As shown, the specific steps for preparing micro / nano copper particles according to the present invention include:

[0043] S11: Prepare the reducing agent solution, primary copper source solution, and secondary copper source solution respectively;

[0044] S12: Mix the copper source solution and the reducing agent solution to obtain the first reaction solution;

[0045] S13: Mix the secondary copper source solution with the first reaction solution to obtain the second reaction solution;

[0046] S14: The second reaction solution is separated and dried to obtain micro / nano copper particles;

[0047] The reducing agent solution and / or the primary copper source solution contain a coating agent.

[0048] First, a primary copper source solution and a reducing agent are mixed to reduce the primary copper source and form copper atoms, which provide nucleation and growth for micro / nano copper particles. Then, a secondary copper source solution is mixed with the first reaction solution to reduce the secondary copper source. Since the oxidation performance of the secondary copper source is weaker than that of the primary copper source, the secondary copper source cannot directly generate copper atoms under the action of the reducing agent. Instead, it can only grow as surface nanocrystals on the surface of micro / nano copper particles, forming micro / nano copper particles with surface protrusion structures. This increases the specific surface area of ​​the micro / nano copper particles and thus improves the sintering activity of the micro / nano copper solder paste.

[0049] In one embodiment, the reducing agent solution contains a coating agent. When the primary copper source solution and the reducing agent solution are mixed and react, the coating agent in the reducing agent solution can coat the micro-nano copper particles generated by the primary copper source reduction, thereby improving the dispersibility of the micro-nano copper particles in the first reaction solution.

[0050] In another embodiment, the primary copper source solution contains a coating agent. When the primary copper source solution is mixed with the reducing agent solution and reacts, the coating agent in the primary copper source solution can coat the micro-nano copper particles generated by the reduction of the primary copper source, thereby improving the dispersibility of the micro-nano copper particles in the first reaction solution.

[0051] Preferably, the reducing agent solution contains a coating agent.

[0052] Specifically, in step S11 above, the step of preparing the reducing agent solution includes:

[0053] S111: Dissolve the coating agent and reducing agent in the first solvent to obtain a reducing agent solution.

[0054] In step S111 above, the present invention does not impose any restrictions on the type of coating agent. For example, the coating agent includes at least one of polyvinylpyrrolidone and hexadecyltrimethylammonium bromide, etc. Such adjustments and changes to the specific type of coating agent do not deviate from the principles and scope of the present invention and should be included within the protection scope of the present invention.

[0055] In some embodiments, the coating agent is hexadecyltrimethylammonium bromide.

[0056] In step S111 above, the concentration of the coating agent is 0.02 mol / L to 1.0 mol / L, for example, the concentration of the coating agent is 0.02 mol / L, 0.1 mol / L, 0.2 mol / L, 0.4 mol / L, 0.5 mol / L, 0.6 mol / L, 0.8 mol / L, 1.0 mol / L, or any range of two of these values. In some embodiments, the concentration of the coating agent is 1.0 mol / L.

[0057] Since the use of coating agents can improve the dispersibility and antioxidant properties of the obtained micro- and nano-copper particles, the particle size of the obtained micro- and nano-copper particles can be adjusted by reasonably adjusting the concentration of the coating agent. That is, using a low concentration of coating agent can obtain micro- and nano-copper particles with larger particle size, while using a high concentration of coating agent can obtain micro- and nano-copper particles with smaller particle size.

[0058] In step S111 above, the present invention does not impose any restrictions on the type of reducing agent. For example, the reducing agent includes at least one of sodium hypophosphite, sodium borohydride, hydrazine hydrate, and ascorbic acid, etc. Such adjustments and changes to the specific type of reducing agent do not deviate from the principles and scope of the present invention and should be included within the protection scope of the present invention.

[0059] In some implementations, the reducing agent is sodium hypophosphite.

[0060] In step S111 above, the concentration range of the reducing agent is 0.4 mol / L to 3.0 mol / L. For example, the concentration of the reducing agent is 0.4 mol / L, 0.6 mol / L, 1.0 mol / L, 1.4 mol / L, 1.6 mol / L, 2.0 mol / L, 2.4 mol / L, 2.6 mol / L, 2.8 mol / L, 3.0 mol / L, or any combination of these values. In some embodiments, the concentration of the reducing agent is 1.6 mol / L.

[0061] The reducing agent can reduce the primary and secondary copper sources to copper atoms, which are used for the nucleation and growth of copper particles and the growth of surface nanostructures. The primary copper source can be ionized to obtain copper ions, which, under the action of the reducing agent, form copper atoms to provide nucleation and growth for micro and nano copper particles. The copper in the secondary copper source is monovalent, and its oxidation performance is weaker than that of divalent copper. Under the action of the reducing agent, it cannot directly generate copper atoms, but can only grow as surface nanocrystals on the surface of micro and nano copper particles to form micro and nano copper particles with surface protrusion structures.

[0062] In step S111 above, the present invention does not impose any restrictions on the type of the first solvent. For example, the first solvent includes at least one of ethylene glycol, polyethylene glycol, diethylene glycol and propylene glycol, etc. Such adjustments and changes to the specific type of the first solvent do not deviate from the principle and scope of the present invention and should be included within the protection scope of the present invention.

[0063] In some embodiments, the first solvent is ethylene glycol.

[0064] Because alcohol solutions have good organic compatibility, they can dissolve most coating agents and reducing agents, and have a high melting point. The solution has a low oxygen content, which can prevent the copper particles from oxidizing during the preparation process.

[0065] In step S11 above, the specific steps for preparing the copper source solution include:

[0066] S112: Dissolve the primary copper source in the second solvent to obtain a primary copper source solution.

[0067] In step S112 above, the present invention does not impose any restrictions on the type of primary copper source. For example, the primary copper source includes at least one of copper sulfate, copper formate, copper acetate, and copper hydroxide, etc. Such adjustments and changes to the specific type of primary copper source do not deviate from the principles and scope of the present invention and should be included within the protection scope of the present invention.

[0068] In some implementations, the primary copper source is copper sulfate.

[0069] In step S112 above, the concentration range of the primary copper source solution is 0.2 mol / L to 1 mol / L. For example, the concentration of the primary copper source solution is 0.2 mol / L, 0.3 mol / L, 0.4 mol / L, 0.5 mol / L, 0.6 mol / L, 0.7 mol / L, 0.8 mol / L, 0.9 mol / L, 1.0 mol / L, or any combination of these values. In some embodiments, the concentration of the primary copper source solution is 0.6 mol / L.

[0070] The particle size of the final micro / nano copper particles can be adjusted by regulating the concentrations of the coating agent solution, the reducing agent solution, and the primary copper source solution.

[0071] In step S112 above, the present invention does not impose any restrictions on the type of the second solvent. For example, the second solvent includes at least one of ethylene glycol, polyethylene glycol, diethylene glycol and propylene glycol, etc. Such adjustments and changes to the specific type of the second solvent do not deviate from the principle and scope of the present invention and should be included within the protection scope of the present invention.

[0072] In some embodiments, the second solvent is ethylene glycol.

[0073] In step S11 above, the step of preparing the secondary copper source solution specifically includes:

[0074] S113: Dissolve the secondary copper source in a third solvent to obtain a secondary copper source solution.

[0075] In step S113 above, the present invention does not impose any restrictions on the type of secondary copper source. For example, the secondary copper source may be at least one of cuprous chloride and cuprous sulfate, etc. Such adjustments and changes to the specific setting of the secondary copper source do not deviate from the principle and scope of the present invention and should be included within the protection scope of the present invention.

[0076] In some implementations, the secondary copper source is cuprous chloride.

[0077] In step S113 above, the concentration range of the secondary copper source is 0.01 mol / L to 0.5 mol / L. For example, the concentration of the secondary copper source is 0.01 mol / L, 0.05 mol / L, 0.1 mol / L, 0.15 mol / L, 0.2 mol / L, 0.25 mol / L, 0.3 mol / L, 0.35 mol / L, 0.4 mol / L, 0.45 mol / L, 0.5 mol / L, or any combination of these values. In some embodiments, the concentration of the secondary copper source is 0.25 mol / L.

[0078] The specific surface area of ​​micro- and nano-copper particles can be adjusted by regulating the concentration of the secondary copper source. When the concentration of the secondary copper source is low, the size of the protrusions formed on the surface of the micro- and nano-copper particles is small, and the specific surface area of ​​the micro- and nano-copper particles is relatively small. When the concentration of the secondary copper source is high, the size of the protrusions formed on the surface of the micro- and nano-copper particles is large, and the specific surface area of ​​the micro- and nano-copper particles is also relatively large.

[0079] In step S113 above, the present invention does not impose any restrictions on the type of the third solvent. For example, the third solvent includes at least one of ethylene glycol, polyethylene glycol, diethylene glycol and propylene glycol, etc. Such adjustments and changes to the specific type of the third solvent do not deviate from the principle and scope of the present invention and should be included within the protection scope of the present invention.

[0080] In some embodiments, the third solvent is ethylene glycol.

[0081] In step S11 above, the present invention does not impose any restrictions on the order of preparation of the reducing agent solution, the primary copper source solution, and the secondary copper source solution. For example, the reducing agent solution can be prepared first, followed by the primary copper source solution, and finally the secondary copper source solution. Alternatively, the primary copper source solution can be prepared first, followed by the reducing agent solution, and finally the secondary copper source solution. Or, the reducing agent solution, the primary copper source solution, and the secondary copper source solution can be prepared simultaneously, and so on. Such adjustments and changes to the order of preparation of the reducing agent solution, the primary copper source solution, and the secondary copper source solution do not deviate from the principles and scope of the present invention and should all be included within the protection scope of the present invention.

[0082] For example, a reducing agent solution is prepared first, then a copper source solution is prepared once, and finally a copper source solution is prepared twice.

[0083] In step S12 above, the primary copper source solution may be added to the reducing agent solution for mixing, or the reducing agent solution may be added to the primary copper source solution for mixing, or the primary copper source solution and the reducing agent solution may be added to another container for mixing, etc. Such adjustments and changes to the specific mixing steps of the primary copper source solution and the reducing agent solution do not deviate from the principles and scope of the present invention, and should all be included within the protection scope of the present invention.

[0084] Preferably, the copper source solution is added to the reducing agent solution for mixing.

[0085] In step S12 above, the reaction time for the copper source solution and the reducing agent solution to react once is 1-2 hours. For example, the reaction time can be 1 hour, 1.2 hours, 1.4 hours, 1.5 hours, 1.6 hours, 1.8 hours, 2 hours, or any combination of these values. In some embodiments, the reaction time for the copper source solution and the reducing agent solution to react once is 1 hour.

[0086] In step S13 above, the secondary copper source solution may be added to the first reaction solution for mixing, or the first reaction solution may be added to the secondary copper source solution for mixing, or the secondary copper source solution and the first reaction solution may be added to another container for mixing, etc. Such adjustments and changes to the specific mixing steps of the secondary copper source solution and the first reaction solution do not deviate from the principle and scope of the present invention, and should all be included within the protection scope of the present invention.

[0087] Preferably, in step S13 above, the secondary copper source solution is added to the first reaction solution for mixing, and the reaction is carried out to obtain the second reaction solution.

[0088] In step S13 above, the reaction time between the secondary copper source solution and the first reaction solution is 1-2 hours. For example, the reaction time can be 1 hour, 1.2 hours, 1.4 hours, 1.5 hours, 1.6 hours, 1.8 hours, 2 hours, or any combination of these values. In some embodiments, the reaction time between the secondary copper source solution and the first reaction solution is 1 hour.

[0089] In step S14 above, the present invention does not impose any particular limitation on the centrifugation speed of the second reaction solution, as long as the micro / nano copper particles can be separated. The centrifugation speed of the second reaction solution is 2000 r / min to 8000 r / min, for example, 2000 r / min, 3000 r / min, 4000 r / min, 5000 r / min, 6000 r / min, 7000 r / min, 8000 r / min, or any combination of these values. In some embodiments, the centrifugation speed of the second reaction solution is 6000 r / min.

[0090] In step S14 above, the second reaction solution is centrifuged 2 to 8 times. For example, the second reaction solution is centrifuged 2, 3, 4, 5, 6, 7, 8 times, or any combination of these values. In some embodiments, the second reaction solution is centrifuged 4 times.

[0091] Centrifugation can remove impurities from the resulting particles. The centrifugation speed and number of centrifugations are coordinated to ensure the purity of the obtained micro-nano copper particles.

[0092] In step S14 above, the present invention does not impose any restrictions on the drying treatment of the micro-nano copper particles after centrifugation. For example, hot air drying or vacuum drying can be performed. Such adjustments and changes to the specific drying method of the micro-nano copper particles after centrifugation do not deviate from the principle and scope of the present invention and should be included within the protection scope of the present invention.

[0093] Preferably, the micro-nano copper particles after centrifugation are vacuum dried.

[0094] By vacuum drying the centrifuged micro- and nano-copper particles, it is possible to obtain dry, low-oxidation micro- and nano-copper particles.

[0095] In step S14 above, the vacuum drying temperature for vacuum drying the centrifuged micro / nano copper particles is 40°C-85°C, for example, 40°C, 50°C, 60°C, 70°C, 80°C, 85°C, or any combination of these values. In some embodiments, the vacuum drying temperature is 60°C.

[0096] In step S14 above, the vacuum drying time for the centrifuged micro / nano copper particles is 0.5h-18h, for example, 0.5h, 2h, 4h, 6h, 8h, 10h, 12h, 14h, 16h, 18h, or any combination of these values. In some embodiments, the vacuum drying time is 8h.

[0097] In step S14 above, the obtained micro / nano copper particles have a particle size range of 50 nm to 1000 nm. For example, the particle size of the micro / nano copper particles is 50 nm, 100 nm, 200 nm, 300 nm, 400 nm, 500 nm, 600 nm, 700 nm, 800 nm, 900 nm, 1000 nm, or any combination of these values. In some embodiments, the particle size of the micro / nano copper particles is 200 nm to 600 nm.

[0098] In step S2 above, the present invention does not impose any restrictions on the type of solder paste additive. For example, the solder paste additive may include at least one of antioxidants and thixotropic agents, or the solder paste additive may include any other possible types, etc. Such adjustments and changes to the specific type of solder paste additive do not deviate from the principles and scope of the present invention and should be included within the protection scope of the present invention.

[0099] Preferably, the solder paste additives include antioxidants and thixotropic agents.

[0100] In step S2 above, the present invention does not impose any restrictions on the type of antioxidant. For example, antioxidants include at least one of ascorbic acid, formic acid, citric acid, glucose and adipic acid, etc. Such adjustments and changes to the specific type of antioxidant do not deviate from the principles and scope of the present invention and should be included within the protection scope of the present invention.

[0101] In some implementations, the antioxidant is citric acid.

[0102] The antioxidant uses highly reducing, acidic organic molecules that can play an antioxidant role during the solder paste sintering process. In addition, the antioxidant has a low melting and boiling point and can volatilize from the solder joint during the sintering process, resulting in low residue.

[0103] In step S2 above, the present invention does not impose any restrictions on the type of thixotropic agent. For example, the thixotropic agent includes at least one of castor oil and polyamide, etc. Such adjustments and changes to the specific type of thixotropic agent do not deviate from the principles and scope of the present invention and should be included within the protection scope of the present invention.

[0104] In some implementations, the thixotropic agent is castor oil.

[0105] Adding thixotropic agents can adjust the thixotropic properties of the slurry.

[0106] In step S2 above, the present invention does not impose any restrictions on the type of organic solvent. For example, the organic solvent includes at least one of ethylene glycol, diethylene glycol, glycerol and α-terpineol, etc. Such adjustments and changes to the specific type of organic solvent do not deviate from the principle and scope of the present invention and should be included within the protection scope of the present invention.

[0107] In some embodiments, the organic solvent is α-terpineol.

[0108] In step S2 above, the total weight percentage of organic solvent, antioxidant, and thixotropic agent is 100%, and the weight percentage of each material in the paste additive is as follows:

[0109] Organic solvents 70%–90%

[0110] Antioxidants 5%–20%

[0111] Thixotropic agent 0.1%–10%.

[0112] By dissolving antioxidants and thixotropic agents in organic solvents, paste additives with different viscosities can be obtained. By adjusting the content of organic solvents, the viscosity of the resulting paste can be adjusted, making the prepared micro / nano copper solder paste suitable for different application scenarios.

[0113] It should be noted that the present invention does not impose any limitation on the weight percentage of the antioxidant. For example, the weight percentage of the antioxidant can be 5%, 10%, 15%, 20%, or any combination of these values. In some embodiments, the weight percentage of the antioxidant is 15%.

[0114] It should also be noted that the present invention does not impose any limitation on the weight percentage of the thixotropic agent. For example, the weight percentage of the thixotropic agent can be 0.1%, 1%, 2%, 5%, 8%, 10%, or any combination of these values. In some embodiments, the weight percentage of the thixotropic agent is 5%.

[0115] It should also be noted that the present invention does not impose any restrictions on the weight percentage of organic solvents, as long as they are able to dissolve the antioxidants and thixotropic agents.

[0116] For example, the antioxidant is 15% by weight, the thixotropic agent is 5% by weight, and the organic solvent is 80% by weight.

[0117] In a second aspect, the present invention also provides a micro / nano copper solder paste, which is prepared by the preparation method described in the first aspect.

[0118] The micro / nano copper solder paste of the present invention comprises micro / nano copper particles and a paste mixing agent, wherein the total weight percentage of the micro / nano copper particles and the paste mixing agent is 100%, and the weight percentages of the micro / nano copper particles and the organic additives are as follows:

[0119] Micro / nano copper particles 50%–85%

[0120] Additives in the ointment: 15%–50%.

[0121] It should be noted that the present invention does not particularly limit the weight percentage of the micro / nano copper particles. For example, the weight percentage of the micro / nano copper particles may be 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, or any combination of these values. In some embodiments, the weight percentage of the micro / nano copper particles is 85%.

[0122] It should also be noted that the present invention does not particularly limit the weight percentage of the compounding agent. For example, the weight percentage of the compounding agent may be 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, or any combination of these values. In some embodiments, the weight percentage of the compounding agent is 15%.

[0123] The preparation method of the micro / nano copper solder paste of the present invention is described in detail below with reference to the following embodiments.

[0124] Example 1:

[0125] The preparation method of micro / nano copper particles in this embodiment includes the following steps:

[0126] S111: Dissolve hexadecyltrimethylammonium bromide (coating agent) and sodium hypophosphite (reducing agent) in ethylene glycol solution and stir at high speed for 1 hour to obtain a reducing agent solution, wherein the concentration of the coating agent is 1 mol / L and the concentration of the reducing agent is 1.6 mol / L;

[0127] S112: Dissolve copper sulfate (primary copper source) in ethylene glycol solution to obtain primary copper source solution, wherein the concentration of primary copper source is 0.6 mol / L;

[0128] S113: Dissolve cuprous chloride (secondary copper source) in ethylene glycol solution to obtain secondary copper source solution, wherein the concentration of secondary copper source is 0.25 mol / L.

[0129] S12: Mix the copper source solution and the reducing agent solution and react for 1 hour to obtain the first reaction solution;

[0130] S13: Mix the secondary copper source solution with the first reaction solution and react for 1 hour to obtain the second reaction solution;

[0131] S14: Centrifuge the second reaction solution and use ultrasound to remove impurities. The centrifugation process is 6000 r / min, and the number of centrifugations is 4. Remove the supernatant from the centrifuged solution, take out the copper particles and vacuum dry them at a temperature of 60℃ for 8 hours.

[0132] S2: Dissolve 15% citric acid and 5% castor oil in α-terpineol to obtain a mixed ointment additive;

[0133] S3: The dried micro / nano copper particles obtained in step S14 are mixed and stirred with the paste mixing agent at a weight ratio of 3:2 (i.e., the weight percentage of micro / nano copper particles is 60% and the weight percentage of paste mixing agent is 40%) to obtain micro / nano copper solder paste.

[0134] Examples 2-11 and Comparative Examples 1-10

[0135] The preparation methods and types of materials for the micro / nano copper solder pastes in Examples 2-11 and Comparative Examples 1-10 are the same as in the Examples. The only difference between Examples 2-11 and Comparative Examples 1-10 and Example 1 is the concentration of the primary copper source solution, the concentration of the secondary copper source solution, the concentration of the reducing agent solution, the concentration of the coating agent solution, and the weight percentage ratio of micro / nano copper particles to the paste additives. That is, Examples 2-11 and Comparative Examples 1-10 are all based on Example 1 by adjusting the concentration of the primary copper source solution, the concentration of the secondary copper source solution, the concentration of the reducing agent solution, the concentration of the coating agent solution, and the weight percentage ratio of micro / nano copper particles to the paste additives. The specific adjustment measures and detailed data are shown in Table 1.

[0136] It should be noted that the weight percentage ratio of micro / nano copper particles to the mixed ointment additives is expressed as: the weight percentage of micro / nano copper particles to the weight percentage of mixed ointment additives.

[0137] For example, the weight percentage ratio of micro / nano copper particles to ointment additives is 3:2, indicating that the weight percentage of micro / nano copper particles is 60% and the weight percentage of ointment additives is 40%.

[0138] The weight percentage ratio of micro / nano copper particles to the mixed paste additives is 1:1, indicating that the weight percentage of micro / nano copper particles is 50% and the weight percentage of the mixed paste additives is 50%.

[0139] The weight percentage ratio of micro / nano copper particles to ointment additives is 17:3, indicating that the weight percentage of micro / nano copper particles is 85% and the weight percentage of ointment additives is 15%.

[0140] The weight percentage ratio of micro / nano copper particles to the mixed ointment additives is 1:2, indicating that the weight percentage of micro / nano copper particles is 33.3% and the weight percentage of mixed ointment additives is 66.7%.

[0141] The weight percentage ratio of micro / nano copper particles to ointment additives is 9:1, indicating that the weight percentage of micro / nano copper particles is 90% and the weight percentage of ointment additives is 10%.

[0142] Table 1:

[0143]

[0144]

[0145] Test method:

[0146] 1. Particle size testing of micro / nano copper particles:

[0147] The particle size of the micro- and nano-copper particles prepared in Examples 1-11 and Comparative Examples 1-10 was determined by using a nano-laser particle size analyzer combined with scanning electron microscopy.

[0148] 2. Scanning electron microscopy (SEM) testing of micro / nano copper particles

[0149] The surface morphology of the micro / nano copper particles was observed using scanning electron microscopy. The scanning electron microscopy image of the micro / nano copper particles in Comparative Example 3 is shown below. Figure 3 Similarly, the scanning electron microscope images of the micro / nano copper particles in Example 4 are similar to... Figure 4 Similarly, the scanning electron microscope images of the micro / nano copper particles in Examples 1 and 5 are similar to those in Examples 5. Figure 5 similar.

[0150] from Figures 3 to 5 It can be seen from this that Figure 3 The micro-nano copper particles in the sample have smooth surfaces and no protruding structures. Figure 4 The smaller protrusions on the surface of the micro / nano copper particles help to increase their specific surface area. Figure 5 The surface of the micro-nano copper particles has a large protrusion structure, which further increases the specific surface area of ​​the micro-nano copper particles.

[0151] 3. Shear strength test of sintered weld joints

[0152] (1) The micro-nano copper solder paste prepared in Examples 1-11 above was printed on a copper substrate with sintering points of 5mm×5mm×1mm through a 100um steel mesh, and a 5mm×5mm×0.2mm gold-plated silicon carbide chip was placed on the solder points. The substrate was dried at 100°C for 60min. The dried substrate material was hot-pressed and sintered in a nitrogen atmosphere. The sintering process conditions were 250°C, 20MPa, and 10min. The shear strength of the sintered solder points was tested according to conventional methods in the art.

[0153] Tests showed that the shear strength of the sintered solder joints of the micro-nano copper solder pastes prepared in Examples 1 to 11 was greater than 25 MPa. This means that the micro-nano copper solder pastes prepared in Examples 1 to 11, when used for sintering gold-plated silicon carbide chips, resulted in high shear strength of the sintered solder joints, meeting the interconnection requirements of chip sintering.

[0154] (2) The micro-nano copper solder paste prepared in Examples 1-11 and Comparative Examples 1-10 was printed on a copper substrate with 5mm×5mm×1mm sintering solder joints through a 100um steel mesh. A 3mm×3mm×1mm copper substrate was placed on top of the solder joints and dried at 100℃ for 60min. The dried substrate material was then hot-pressed and sintered in a nitrogen atmosphere. The sintering process conditions were 250℃, 20MPa, and 10min.

[0155] The micro-nano copper solder pastes prepared in Examples 1-11 and Comparative Examples 1-10 were subjected to shear strength tests on the sintered solder joints after sintering using conventional methods in the art. The shear strength tests all showed a value greater than 40 MPa, which meets the requirements for chip sintering interconnection. The specific test results are shown in Table 2.

[0156] Table 2:

[0157]

[0158]

[0159] The data in Table 2 shows that:

[0160] 1. Comparing Examples 1 to 3 with Comparative Examples 1 to 2, when the concentration of the primary copper source solution is too low, the particle size of the prepared micro / nano copper particles is too large, the specific surface area of ​​the micro / nano copper particles is small, the sintering activity of the prepared micro / nano copper solder paste is also low, and the shear strength of the sintered solder joint is also relatively low. As the concentration of the primary copper source increases, the particle size of the prepared micro / nano copper particles gradually decreases, the specific surface area of ​​the micro / nano copper particles gradually increases, the sintering activity of the prepared micro / nano copper solder paste increases, and the shear strength of the sintered solder joint also increases further. However, when the concentration of the primary copper source increases to a certain level, although the particle size of the prepared micro / nano copper particles will further decrease, the excessively small particle size will make the micro / nano copper particles more susceptible to oxidation, and the sintering activity of the prepared micro / nano copper solder paste will further decrease, and the shear strength of the sintered solder joint will also further decrease. Therefore, controlling the concentration of the primary copper source solution within a suitable range can result in higher shear strength of the sintered solder joint of the prepared micro / nano copper solder paste.

[0161] Since the shear strength of the sintered solder joints in Examples 1 to 3 is much higher than that in Comparative Examples 1 and 2, when the concentration of the copper source solution is 0.2 mol / L to 1 mol / L, the particle size of the prepared micro / nano copper particles can be controlled within a suitable range, and the sintered solder joints of the prepared micro / nano copper solder paste have high shear strength.

[0162] Furthermore, since the shear strength of the sintered solder joint in Example 1 is higher than that in Examples 2 and 3, when the concentration of the primary copper source solution is 0.6 mol / L, the prepared micro-nano copper particles have a moderate particle size and a low degree of oxidation, and the sintered solder joint of the prepared micro-nano copper solder paste has a high shear strength.

[0163] 2. Comparing Examples 1, 4, and 5 with Comparative Examples 3 and 4, although the particle size of the prepared micro / nano copper particles did not change significantly with the increase of the concentration of the secondary copper source solution, the size of the surface protrusions of the prepared micro / nano copper particles increased, resulting in an increase in the specific surface area of ​​the prepared micro / nano copper particles and enhanced sintering activity. The sintered solder joints of the prepared micro / nano copper solder paste had high shear strength after sintering. However, when the concentration of the secondary copper source solution increased to a certain level, the surface protrusions of the prepared micro / nano copper particles became too large, which led to a decrease in the specific surface area of ​​the micro / nano copper particles, thereby reducing the shear strength of the sintered solder joints of the prepared micro / nano copper solder paste after sintering. Therefore, controlling the concentration of the secondary copper source solution within a suitable range can result in higher shear strength of the sintered solder joints of the prepared micro / nano copper solder paste after sintering.

[0164] Since the shear strength of the sintered solder joints of the micro-nano copper solder pastes prepared in Examples 1, 4 and 5 is significantly higher than that in Comparative Examples 3 and 4, when the concentration of the secondary copper source solution is 0.01 mol / L-0.5 mol / L, the protrusion structure on the surface of the prepared micro-nano copper particles is moderate, and the specific surface area of ​​the micro-nano copper particles is large, thus resulting in better performance of the prepared micro-nano copper solder paste.

[0165] Furthermore, since the shear strength of the sintered solder joint in Example 1 is higher than that in Examples 4 and 5, the micro / nano copper solder paste prepared has better performance when the concentration of the secondary copper source solution is 0.25 mol / L.

[0166] 3. Comparing Examples 1, 6, and 7 with Comparative Examples 5 to 6, as the concentration of the reducing agent increases, the particle size of the prepared micro / nano copper particles gradually decreases, the sintering activity of the prepared micro / nano copper solder paste gradually increases, and the shear strength of the sintered solder joints is high. However, when the concentration of the reducing agent increases to a certain level, the particle size of the prepared micro / nano copper particles further decreases. But if the particle size of the micro / nano copper particles is too small, the micro / nano copper particles will be more easily oxidized, and the sintering activity of the prepared micro / nano copper solder paste will further decrease, and the shear strength of the sintered solder joints will also further decrease. Therefore, controlling the concentration of the reducing agent solution within a suitable range can make the sintered solder joints of the prepared micro / nano copper solder paste have high shear strength.

[0167] Since the shear strength of the sintered solder joints in Examples 1, 6 and 7 is higher than that in Comparative Examples 5 to 6, when the concentration of the reducing agent solution is 0.4 mol / L to 3 mol / L, the particle size of the prepared micro / nano copper particles can be controlled within a suitable range, resulting in better performance of the prepared micro / nano copper solder paste.

[0168] Furthermore, since the shear strength of the sintered solder joint in Example 1 is higher than that in Examples 6 and 7, when the concentration of the reducing agent solution is 1.6 mol / L, the prepared micro-nano copper particles have a moderate particle size and a low degree of oxidation, and the sintered solder joints of the prepared micro-nano copper solder paste have a high shear strength after sintering.

[0169] 4. Comparing Examples 1, 8 to 9 with Comparative Examples 7 to 8, as the concentration of the coating agent increases, the particle size of the prepared micro / nano copper particles gradually decreases, the sintering activity of the micro / nano copper solder paste increases, and the shear strength of the sintered solder joint gradually increases. However, when the concentration of the coating agent increases to a certain level, the particle size of the prepared micro / nano copper particles does not decrease significantly, and the shear strength of the sintered solder joint does not increase significantly. If the concentration of the coating agent is too high, the preparation cost of the micro / nano copper solder paste will be high. Therefore, controlling the concentration of the coating agent within a suitable range will result in a micro / nano copper solder paste with good performance and low cost.

[0170] Since the shear strength of the sintered solder joints in Examples 1, 8 to 9 is significantly higher than that in Comparative Example 7, although the shear strength of the sintered solder joint in Comparative Example 8 is not much different from that in Example 1, the particle size of the prepared micro / nano copper particles does not decrease significantly with the further increase of the coating agent concentration, and the shear strength of the sintered solder joint does not increase significantly. Increasing the coating agent concentration will increase the preparation cost of micro / nano copper particles. Therefore, when the coating agent concentration is 0.02 mol / L to 1 mol / L, the prepared micro / nano copper solder paste has better performance and lower cost.

[0171] Furthermore, since the shear strength of the sintered solder joint in Example 1 is higher than that in Examples 8 and 9, the micro-nano copper solder paste prepared has better performance when the coating agent concentration is 1 mol / L.

[0172] 5. Comparing Examples 1, 10, and 11 with Comparative Examples 9 to 10, as the weight percentage ratio of micro / nano copper particles to paste additives increases, the proportion of micro / nano copper particles gradually increases, the sintering activity of the prepared micro / nano copper solder paste improves, and the shear strength of the sintered solder joints also gradually increases. When the weight percentage ratio of micro / nano copper particles to paste additives increases to a certain level, the proportion of micro / nano copper particles is too high, resulting in excessively high viscosity of the micro / nano copper solder paste, which is not conducive to sintering, and the shear strength of the sintered solder joints is also relatively low. Therefore, controlling the weight percentage ratio of micro / nano copper particles to paste additives within a suitable range can result in better performance of the prepared micro / nano copper solder paste.

[0173] Since the shear strength of the sintered solder joints in Examples 1, 10 and 11 is significantly higher than that in Comparative Examples 9 and 10, the micro-nano copper solder paste prepared has better performance when the weight percentage ratio of micro-nano copper particles to paste additives is (1:1) to (17:3), that is, when the weight percentage of micro-nano copper particles is 50% to 85% and the weight percentage of paste additives is 15% to 50%.

[0174] Furthermore, since the shear strength of the sintered solder joint in Example 1 is higher than that in Examples 10 and 11, the micro-nano copper solder paste prepared has better performance when the weight percentage ratio of micro-nano copper particles to paste additives is 3:2, that is, when the weight percentage of micro-nano copper particles is 60% and the weight percentage of paste additives is 40%.

[0175] The technical solution of the present invention has been described above with reference to the preferred embodiments shown in the accompanying drawings. However, it will be readily understood by those skilled in the art that the scope of protection of the present invention is obviously not limited to these specific embodiments. Without departing from the principles of the present invention, those skilled in the art can make equivalent changes or substitutions to the relevant technical features, and the technical solutions after such changes or substitutions will all fall within the scope of protection of the present invention.

Claims

1. A method for preparing micro / nano copper solder paste, characterized in that, The preparation method includes the following steps: S1: Preparation of micro / nano copper particles; S2: Dissolve the solder paste additive in an organic solvent to obtain a mixed paste additive; S3: Mix micro / nano copper particles with paste additives to prepare micro / nano copper solder paste; The micro-nano copper particles are obtained by sequential reduction using a primary copper source and a secondary metal source, wherein the oxidation capacity of the secondary metal source is less than that of the primary copper source. The secondary metal source is a secondary copper source, and the specific steps for preparing micro / nano copper particles include: S11: Prepare the reducing agent solution, primary copper source solution, and secondary copper source solution respectively; S12: The primary copper source solution and reducing agent solution are mixed and reacted to obtain the first reaction solution; S13: The secondary copper source solution is mixed with the first reaction solution to obtain a second reaction solution; S14: The second reaction solution is separated and dried to obtain micro-nano copper particles; The reducing agent solution and / or the primary copper source solution contain a coating agent; The primary copper source includes at least one of copper sulfate, copper formate, copper acetate, and copper hydroxide; The secondary copper source includes at least one of cuprous chloride and cuprous sulfate.

2. The method for preparing micro / nano copper solder paste according to claim 1, characterized in that, In step S11 above, the step of preparing the reducing agent solution specifically includes: The coating agent and reducing agent are dissolved in the first solvent to obtain a reducing agent solution; And / or, the specific steps for preparing a copper source solution include: The primary copper source is dissolved in the second solvent to obtain the primary copper source solution; And / or, the steps for preparing the secondary copper source solution specifically include: The secondary copper source is dissolved in a third solvent to obtain a secondary copper source solution.

3. The method for preparing micro / nano copper solder paste according to claim 2, characterized in that, The coating agent includes at least one of polyvinylpyrrolidone and hexadecyltrimethylammonium bromide; And / or, the reducing agent includes at least one of sodium hypophosphite, sodium borohydride, hydrazine hydrate, and ascorbic acid.

4. The method for preparing micro / nano copper solder paste according to claim 2, characterized in that, The first solvent and / or the second solvent and / or the third solvent include at least one of ethylene glycol, polyethylene glycol, diethylene glycol and propylene glycol.

5. The method for preparing micro / nano copper solder paste according to claim 1, characterized in that, The concentration range of the coating agent is 0.02 mol / L to 1.0 mol / L; And / or, the concentration range of the reducing agent is 0.4 mol / L to 3.0 mol / L; And / or, the concentration range of the primary copper source solution is 0.2 mol / L to 1 mol / L; And / or, the concentration range of the secondary copper source solution is 0.01 mol / L to 0.5 mol / L.

6. The method for preparing micro / nano copper solder paste according to claim 1, characterized in that, In step S2 above, the solder paste additive includes at least one of an antioxidant and a thixotropic agent; And / or, the organic solvent includes at least one of ethylene glycol, diethylene glycol, glycerol, and α-terpineol.

7. The method for preparing micro / nano copper solder paste according to claim 6, characterized in that, In step S2 above, the ointment additive satisfies at least one of the following conditions: The antioxidants include at least one of ascorbic acid, formic acid, citric acid, glucose, and adipic acid; The thixotropic agent includes at least one of castor oil and polyamide; The total weight percentage of the organic solvent, the antioxidant, and the thixotropic agent is 100%, wherein the weight percentage of the organic solvent is 70% to 90%, the weight percentage of the antioxidant is 5% to 20%, and the weight percentage of the thixotropic agent is 0.1% to 10%.

8. The method for preparing micro / nano copper solder paste according to any one of claims 1 to 7, characterized in that, The particle size range of the micro-nano copper particles is 50nm~1000nm.

9. A micro / nano copper solder paste, characterized in that, The micro / nano copper solder paste is prepared by the preparation method according to any one of claims 1 to 8, wherein the micro / nano copper solder paste comprises micro / nano copper particles and a paste mixing agent, the total weight percentage of the micro / nano copper particles and the paste mixing agent is 100%, and the weight percentages of the micro / nano copper particles and the paste mixing agent are as follows: Micro / nano copper particles 50% ~ 85% Additives in the ointment: 15% ~ 50%.

Citation Information

Patent Citations

  • Method for manufacturing ultra-fine copper powder

    CN103878388A

  • Preparation method of flower-like nano-copper

    CN107498068A